(untitled) (Acta Polytechnica CTU Proceedings, 2022)
The presented research focuses on the behavior of predried concrete beams with 2.5 m span subjected to cycles of nonsymmetric wetting and drying. Wetting is induced by partially immersing the specimens in a water basin. The submerged portion of the specimens was relatively low (1/5 to 1/10 of their height) leading to a highly nonuniform and nonsymmetric distribution of eigenstrains due to concrete swelling. Unlike conventional experiments on the volume changes of concrete, the measured quantity is not the axial deformation but the vertical displacement instead. This paper presents the experimental data obtained within two wetting and drying cycles, running over 1 year.